2010
DOI: 10.1371/journal.pone.0011462
|View full text |Cite
|
Sign up to set email alerts
|

Superparamagnetic Iron Oxide Nanoparticles Labeling of Bone Marrow Stromal (Mesenchymal) Cells Does Not Affect Their “Stemness”

Abstract: Superparamagnetic iron oxide nanoparticles (SPION) are increasingly used to label human bone marrow stromal cells (BMSCs, also called “mesenchymal stem cells”) to monitor their fate by in vivo MRI, and by histology after Prussian blue (PB) staining. SPION-labeling appears to be safe as assessed by in vitro differentiation of BMSCs, however, we chose to resolve the question of the effect of labeling on maintaining the “stemness” of cells within the BMSC population in vivo. Assays performed include colony formin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
67
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 26 publications
5
67
0
Order By: Relevance
“…[94][95][96][97] We were able to obtain chondrogenic, osteogenic, and adipogenic differentiation of mesenchymal stem cells after SPION labeling. 15 More recently, Balakumaran et al 98 successfully demonstrated the potential of SPI-ON-labeled stem cells to appropriately differentiate in vivo. Figure 2 shows Feridex-labeled mesenchymal stem cells harvested from bone marrow of Wistar rats, which are differentiated into adipocytes and chondrocytes.…”
mentioning
confidence: 99%
“…[94][95][96][97] We were able to obtain chondrogenic, osteogenic, and adipogenic differentiation of mesenchymal stem cells after SPION labeling. 15 More recently, Balakumaran et al 98 successfully demonstrated the potential of SPI-ON-labeled stem cells to appropriately differentiate in vivo. Figure 2 shows Feridex-labeled mesenchymal stem cells harvested from bone marrow of Wistar rats, which are differentiated into adipocytes and chondrocytes.…”
mentioning
confidence: 99%
“…It has also been suggested that BMSC stemness under various conditions may be defined as the ability to differentiate in vivo and support hematopoietic elements [37]. Superparamagnetic iron oxide nanoparticle labeling of BMSCs does not affect their stemness [38]. In the current study, it was evident that BMSCs had a significantly greater proliferation rate when grown in low oxygen tension compared with normoxia after an initial lag phase.…”
Section: Figmentioning
confidence: 52%
“…Superparamagnetic iron oxide nanoparticles (SPIONs) are U.S. Food and Drug Administration-approved MRI contrast agents and are already used in clinics; thus they are reasonable candidates for in vivo imaging in tissue engineering and regenerative medicine. Various cells, for example, adipocytes, mesenchymal stem cells, neural stem cells (NSCs), human adipose-derived stromal cells, chondrocytes, and smooth muscle cells, can be easily labeled with SPIONs [55][56][57][58][59]. In addition to cells, SPIONs can be incorporated into engineered scaffolds before implantation, and their location and degradation can be monitored using MRI [17].…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%